Increasing foreign direct investments to Kenya: an analysis of underlying factors - Schützeichel, Paul Maria (Strathmore University, 2013)
This research studied a 14 year period of FDI inflows to Kenya (1998-2011) while especially focusing on the seven year period of increasing FDI inflows from 2005 to 2011. Prior to this period of growth, a trend of stagnating FDI inflows can be observed thus raising the question what factors exactly contributed to the rising FDI inflows. The study included two types of analyses: (1) an analysis of publicly available indices and (2) an analysis of primary data collected through questionnaires which intended to confirm or dismiss the findings of the secondary analysis. Through these analyses, the study revealed that the factors for the increasing FDI inflows were: Kenya’s role as regional hub and the increasing regional cooperation and integration, increasing market size and level of education, innovation and technology embraced within the local market, the ease of doing business in Kenya and infrastructure development. Surprisingly, other factors such as political stability, inflation, rule of law and corruption levels even deteriorated during the period of growth. In general, this research was conducted to explain the reasons behind the increasing FDI inflows to Kenya and thus reveals important information for fellow researchers, policy makers and foreign companies. The implications of the study were for the government to strongly focus on increased regional cooperation and integration and to further improve the ease of doing business among others. This research contributes to existing knowledge by establishing factors for increasing FDI inflows to developing countries in general and Kenya in specific.
Submitted in partial fulfillment of the requirements for the Degree of a Master of Commerce
Keywords: Foreign Direct Investments; Kenya